Analysis of Community Participation of World Cleanup Day Activities and Waste Composition in Amal Lama Beach, Tarakan - Gazali Salim; Agus Indarjo; Ridwan Shabir; Asriadi; Ayu Tri Fatma; Rezkyana; Suriyanti; Nabila; Rukisah; Achmad Daengs GS (Future Science, 2019)
The purpose of this service is the analysis of community participation in world cleanup day activities and the composition of waste on the Amal Lama Beach, Tarakan. The sampling method is based on a random sampling method, wherein the sampling is in accordance with the awareness and awareness of the community regarding environmental cleanliness in the old charity coastal area of Tarakan city. Retrieval of data based on the attendance results of attendance world cleanup day activities based on age, based on sex, based on the participating agency activities and based on the type of waste. The results of the study after World Cleanup Day activities found 4 different types of waste, namely the type of waste from the community / local residents amounting to 385 kg with a percentage of about 45.45%; types of local tourist waste amounted to 16kg with a percentage of about 1.89%; types of waste from nature amounting to 254 kg with a percentage of about 29.99%; type of waste from seaweed cultivation is 192 kg with a percentage of about 22.67%.